The international handbook of social enterprise law : benefit corporations and other purpose-driven companies - Peter, Henry; Vargas Vasserot, Carlos; Alcalde Silva, Jaime (Springer, 2023)
"This open-access book brings together international experts who shed new light on the status of social enterprises, benefit corporations and other purpose-driven companies. The respective chapters take a multidisciplinary approach (combining law, philosophy, history, sociology and economics) and provide valuable insights on fostering social entrepreneurship and advancing the common good. In recent years, we have witnessed a significant shift of how business activities are conducted, mainly through the rise of social enterprises. In an effort to target social problems at their roots, social entrepreneurs create organizations that bring transformative social changes by considering, among others, ethical, social, and environmental factors. A variety of social enterprise models are emerging internationally and are proving their vitality and importance. But what does the term 'social enterprise' mean? What are its roots? And how does it work in practice within the legal framework of any country? This handbook attempts to answer these questions from a theoretical, historical, and comparative perspective, bringing together 44 contributions written by 71 expert researchers and practitioners in this field. The first part provides an overview of the social enterprise movement, its evolution, and the different forms entities can take to meet global challenges, overcoming the limits of what governments and states can do. The second part focuses on the emergence of benefit corporations and the growing importance of sustainability and societal values, while also analyzing their different legal forms and adaptation to their regulatory environment. In turn, the last part presents the status quo of purpose-driven companies in 36 developed and emerging economies worldwide"--Publisher's description.